KETERLIBATAN KARYAWAN DAN MOTIVASI INTRINSIK UNTUK MENINGKATKAN KINERJA KARYAWAN MELALUI DISIPLIN KERJA - Magdalena, Betty; Suwandi, Suwandi; Utami, Riyandini Riyan; Aminah, Aminah (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
Based on the performance condition of Asoka Luxury hotel employees, there is a problem because employee performance appraisals are still far from the targets set by the company, this causes the company's profits to decrease. This study aims to determine the effect of Employee Engagement, and Intrinsic Motivation on Performance through Work Discipline. The type of research used in this study is a type of quantitative research using associative methods, namely using a partial least square approach where the processing uses PLS software. The data collection method in this study used primary data in the form of interviews and questionnaire distribution. The population in this study was 35 employees using saturated sampling techniques, where the entire population was sampled. The results of this study found that work involvement affects the performance of Asoka Luxury Bandar Lampung Hotel employees. Intrinsic Motivation Affects the Performance of Hotel Asoka Luxury Bandar Lampung Employees.Work Involvement Affects Performance through Work Discipline of Hotel Asoka Luxury Bandar Lampung Employees. Intrinsic Motivation Affects Performance through Work Discipline of Asoka Luxury Hotel Bandar Lampung Employees.